Heat island effect for Nicosia, Cyprus - Theophilou, Marios; Serghides, Despina Kyprianou (My University, 2014)
Daily values of meteorological data from two stations, one rural and one urban, of Cyprus Meteorological Service for a very large period (1983-2010) have been analyzed in order to detect the existence of the heat island effect in Nicosia, Cyprus. This study examines the heat island effect by comparing the mean daily temperature of the two stations - rural and urban - for three different decades, 1983-1990, 1991-2000 and 2000-2010. The analysis shows the existence of the heat island effect for all three periods of study with an intensity of 6.8°C for 1983-1990, 6.2°C for 1991-2000 and 3.5°C for 2001-2010, which are also statistically significant. The heat island effect is also being examined seasonally - winter and summer periods - and with respect to three different categories of wind speed - less than 2.5 m/s, less than 5.0 m/s and less than 10.0 m/s and it was found that the heat island effect is a winter phenomenon and that the intensity is larger when the wind speed is smaller. The daily analysis for one year shows also that the phenomenon is larger during the day rather during the night. The selection of the stations is based on the deletion of any differences between the stations regarding the height above sea level, the soil morphology and the station orientation. The specific urban station has been selected in order to cover a large variety of areas, such as city center, dense built-up areas and large roads with high buildings while the specific rural station is situated in an area outside the city. For the statistical significance of the any trend analyzed in this paper, the Mann-Kendall trend test was used. © 2014
Keywords: Heat island; Temperature; Wind speed